Early Test Effort Prediction using UML Diagrams - Pulak Sahoo; J R Mohanty (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Software Testing is essential for delivering quality software products. Accurate test effort estimation is an important part of project planning. Prediction of test effort at early phases of Software Developmen Life Cycle enables managers to plan ahead for the testing phase. This increases the chances of the project meeting its timeline while achieving required quality. Unified Modeling Language is a widely-used standard for representing Object Oriented Systems. Use Case and Class Diagrams are two of the most important models of the system created during early phases of software development. This work proposed that the initial test effort is predicted early using Use Case Diagram during the requirement stage and is refined during design stage when Class Diagrams are available. The predicted test efforts in both stages are functions of parameters derived from Use Case and Class Diagrams. Estimations can be revised when rest of the UML diagrams are created.